The Role of Information Technology in Optimizing Zakat Management - Evra Willya; Zainal Arifin; Elis Mediawati; Sabil Mokodenseho (West Science Islamic Studies, 2023)
This research investigates the role of Information Technology (IT) in optimizing Zakat management in Indonesia, the world's largest Muslim-majority country. Employing a mixed-methods approach, qualitative insights from in-depth interviews and quantitative data from surveys were integrated to provide a comprehensive understanding of the current state of IT integration, challenges faced, perceived benefits, and its impact on Zakat distribution processes. The findings reveal a spectrum of IT adoption among Zakat organizations, with cybersecurity concerns, resistance to change, and resource constraints identified as persistent challenges. Perceived benefits include enhanced transparency, streamlined distribution processes, and improved communication with beneficiaries. Statistical analysis supports a positive correlation between IT integration levels and perceived improvements in distribution fairness and effectiveness. The implications and recommendations drawn from these integrated insights guide stakeholders in optimizing Zakat administration through effective and secure IT adoption, aligning with principles of transparency, efficiency, and equitable distribution.